Longitudinal Investigations of Autoregressive Cross-Lagged Path Models Among Internet Use, Executive Function Problems, and Maternal Control in Young Korean Children - Song, Hana (Frontiers in Psychiatry, 2022)
Excessive Internet use is related to behavioral and cognitive dysfunctions, but little is known about the relationship between them in young children. This study examined the longitudinal relationship between children’s Internet use, executive function problems, and maternal control. Differences by children’s Internet addiction status in their associations were also examined. Data from Wave 9 (2016) to Wave 11 (2018) of 1,463 children and mothers who participated in the Panel Study on Korean Children (PSKC) were used. The children’s ages were 8 (grade 2), 9 (grade 3), and 10 years (grade 4) at Waves 9, 10, and 11, respectively. Associations between the variables were analyzed using autoregressive cross-lagged model estimations and multi-group analysis. The results showed the longitudinal stability of each of children’s Internet use, executive function problems, and maternal control over the three years. Mutual associations between maternal control and children’s Internet use were found. In addition, children’s executive function problems positively predicted Internet use, and negative associations from executive function problems to maternal control were significant over the years. However, some of the associations were significant only in the high-risk group. Discussions have focused on the protective role of maternal control, which could reduce children’s Internet use and impulsive behavioral problems.